2019
DOI: 10.1084/jem.20190186
|View full text |Cite
|
Sign up to set email alerts
|

CD81 is a novel immunotherapeutic target for B cell lymphoma

Abstract: The anti-CD81 mAb (5A6) eliminates lymphoma tumor cells from patient follicular biopsy specimens while sparing the imbedded normal B and T lymphocytes. It has equivalent therapeutic effects as rituximab against a xenografted human B cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Tetraspanins are emerging therapeutic targets for cancers, as multiple family members (e.g., CD81, CD53, CD9, CD151, TSPAN8, and CD37) have been implicated in tumor initiation, promotion, and/or metastasis (de Winde et al, 2017;Vences-Catalán & Levy, 2018;Bonnet et al, 2019;Vences-Catalán et al, 2019). CD81, for example, is expressed in a variety of solid tumors and hematopoietic malignancies, and loss of CD81 inhibits the invasion and metastasis of melanoma, breast, and lung tumor cells (Vences-Catalán et al, 2015).…”
Section: Cd53-assisted B-cell Migrationmentioning
confidence: 99%
“…Tetraspanins are emerging therapeutic targets for cancers, as multiple family members (e.g., CD81, CD53, CD9, CD151, TSPAN8, and CD37) have been implicated in tumor initiation, promotion, and/or metastasis (de Winde et al, 2017;Vences-Catalán & Levy, 2018;Bonnet et al, 2019;Vences-Catalán et al, 2019). CD81, for example, is expressed in a variety of solid tumors and hematopoietic malignancies, and loss of CD81 inhibits the invasion and metastasis of melanoma, breast, and lung tumor cells (Vences-Catalán et al, 2015).…”
Section: Cd53-assisted B-cell Migrationmentioning
confidence: 99%
“…In addition, dysregulation of normal tetraspanin function leads to diseases like cancer, diabetes, Alzheimer's and autoimmune reactions [3,4]. This, coupled with their easy accessibility as membrane proteins, means that tetraspanins have a huge potential to serve as therapeutic targets for the development of new treatments in cancer, hematological malignancies and infectious diseases [5][6][7][8].…”
mentioning
confidence: 99%
“…Adding natural killer (NK) cells to the in vitro assay revealed that 5A6 also efficiently mediates antibody-dependent cell cytotoxicity (ADCC). Considering that mouse IgG1 is not efficient in activating complement, Vences-Catalán et al (2019) tested whether the killing efficiency of 5A6 could be augmented by substituting the constant region of IgG1 heavy chain with either mouse IgG2a or human IgG1 constant regions. Indeed, both modified 5A6 antibodies showed strong complement-dependent cytotoxicity (CDC), whereas the original mouse IgG1 5A6 showed little CDC.…”
mentioning
confidence: 99%
“…The data presented in the comprehensive work by Vences-Catalán et al (2019) are promising and might even be of relevance beyond the therapy of lymphomas, because CD81 is also highly expressed on many solid cancers, so that such tumors may principally be considered for an immunotherapy targeting CD81 (Vences-Catalán et al, 2017). Nevertheless, a number of caveats need to be considered, and further studies are essential before it will become clear whether anti-CD81 immunotherapy is indeed a suitable therapeutic strategy for B cell lymphomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation